Behavior of Nutritional Supplements Use in Association With Inflammatory Skin Diseases in Chinese College Students - Yuan, Yan; Su, Juan; Li, Ji; Tao, Juan; Kang, Xiaojing; Wu, Bin; Shan, Shijun; Wang, Xiaohui; Chen, Xiang; Shen, Minxue; Jiang, Liyuan (Frontiers in Nutrition, 2021)
Abstract Objectives: It is understudied how frequent adolescents use nutritional supplements (NS) and whether the behaviour is associated with skin diseases that may cause unpleasant symptoms and disfigurement. The current study aimed to investigate the prevalence of NS use in Chinese college students and its association with inflammatory skin diseases. Methods: This was a university-based epidemiologic investigation that included 20138 students who underwent dermatological examinations and a questionnaire survey inquiring about the use of NS and related information. Skin diseases were diagnosed by dermatologists during the health examination. Logistic regression models were used, and adjusted odds ratios (aORs) were presented as the effect size. Results: A total of 20138 participants survey responses were analyzed. 18.3% of the participants reported the use of NS in the past year. The use of vitamin C was the most frequently reported with a proportion of 12.9%, followed by vitamin B and mineral supplements. The use of NS was associated with female sex, Han ethnicity, higher annual household income, and a series of healthy lifestyle, such as more physical activity, less second hand smoke exposure, less alcohol consumption, and more intake of milk and yogurt (p<0.001). Participants with chronic urticaria (aOR=1.3; 95% CI: 1.0–1.7), atopic dermatitis (aOR=1.4; 95% CI: 1.2–1.6) or acne (aOR=1.17; 95% CI: 1.04–1.31) were more likely to use NS, especially herb (aOR=2.7; 95% CI: 1.2–3.7), followed by vitamin B (aOR=1.6; 95% CI: 1.2–2.0) and mineral supplements (aOR=1.4; 95% CI: 1.0–2.0). Conclusion: College students with inflammatory skin disease are more likely to use NS.